Long-range Transport, Regional Forest Fire Events and Meteorological Influences on PM2.5 in Western Nepal - Maharjan, Nabina; Lamichhane, Govinda Prasad; Timalsina, Niroj; Paudel, Shankar Prasad; Sapkota, Ramesh Prasad (Geographical Journal of Nepal, 2026)
PM2.5 pollution is a major global environmental concern, upsetting human as well as ecosystem health. This study examines the long-range transport and effects of meteorological factors on PM2.5 concentration, utilizing data from a real-time air quality monitoring station established in the Rara National Park in 2020 and satellite data. Similarly, the influence of forest fire events on PM2.5 levels were also assessed. PM2.5 concentration at the Rara Station showed bimodal pattern, higher during early morning and late night, with peak levels in March and April, particularly due to forest fires in regional geographical extent. The correlation between PM2.5 and meteorological factors showed a moderate negative relationship with humidity, and weak negative and positive correlation with temperature and wind speed, respectively. Wind direction analysis indicated that southern and southwestern air masses significantly contributed to elevated PM2.5 levels, suggesting regional and transboundary transport of pollutants. The strong correlation between fire frequency and PM2.5 concentration was observed around 100-200 km at 2-day time lag emphasizing the long-range transport of pollutants. Linear regression model indicated that forest fires had a significant impact on air quality, explaining about 74% of the variance in PM2.5 levels. Linear regression analysis further indicated that forest fire frequency explained a substantial portion of PM2.5 variability, with each additional fire within 100 km increasing PM2.5 by 0.4 μg m-3. The findings highlight regional approach and transboundary cooperation for research and policy interventions to mitigate regional forest fire events and improve regional and local air quality.